Rotating Machinery, Optical Methods & Scanning LDV Methods, Volume 6 Proceedings of the 39th IMAC, A Conference and Exposition on Structural Dynamics 2021 - Di Maio, Dario; Baqersad, Javad; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Rotating Machinery, Optical Methods & Scanning LDV Methods, Volume 6: Proceedings of the 39th IMAC, A Conference and Exposition on Structural Dynamics, 2021, the sixth volume of nine from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Health Monitoring, including papers on: Novel Techniques Optical Methods, Scanning LDV Methods Photogrammetry & DIC Rotating Machinery.
Keywords: Machinery; Microscopy; Aerospace engineering; Astronautics; Algorithms; Mathematics -- Data processing; Machinery and Machine Elements; Optical Microscopy; Aerospace Technology and Astronautics; Algorithms; Computational Mathematics and Numerical Analysis; Mechanical engineering -- Congresses; Rotational motion -- Congresses